Exploring trends in employer attractiveness research: A bibliometric coupling approach - Tran Thi Siem; Ho Thi Thao Nguyen; Anh Tho To; Thai Kim Phong (Acta Psychologica, 2025)
Employer attractiveness is a subject that has not been as extensively explored as other research topics. This study aims to provide an overview of research trends on employer attractiveness and identify gaps that could inspire new research ideas. This study leverages the Scopus database and employs bibliometric analysis using VOSviewer software. The findings reveal four primary themes in employer attractiveness research: indicators reflecting employer attractiveness, the application of employer attractiveness in communication strategies to attract potential candidates, organizational attractiveness in the public sector, and the relationship between internal communication and employer branding. This paper aids researchers in gaining a deeper understanding of employer attractiveness research trends to facilitate subsequent studies.